2012
DOI: 10.4103/0019-5413.104213
|View full text |Cite
|
Sign up to set email alerts
|

Double parabolic Kirschner-wires as dynamic distractor for treatment of unstable intraarticular phalangeal fractures of hand

Abstract: Background:Treatment of complex injuries of interphalangeal joints (IPJs) is difficult. The restoration of joint stability for early joint mobility till fracture union is the key for successful outcome. Although various treatment options like dynamic splinting, external fixator, closed reduction, transarticular Kirschner (K)-wire and ORIF, etc., are available in literature, a universally accepted ideal treatment for complex intraarticular fractures of IPJs is still evolving. Open reduction is difficult because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Numerous reports using external fixators showed a mean range of motion in the PIP joint between 64° and 91° similar to this report with app. 76° [14,[20][21][22]. The patient cohort in this study showed a moderate acceptance of the external fixator, however, a high satisfaction at final follow-up with very mild discomfort (VAS 0.7).…”
Section: Discussionmentioning
confidence: 56%
“…Numerous reports using external fixators showed a mean range of motion in the PIP joint between 64° and 91° similar to this report with app. 76° [14,[20][21][22]. The patient cohort in this study showed a moderate acceptance of the external fixator, however, a high satisfaction at final follow-up with very mild discomfort (VAS 0.7).…”
Section: Discussionmentioning
confidence: 56%
“…K-wires are easily removed after 4 to 6 weeks depending on type of fracture, and removal doesn't require hospitalization. 5,7,9,11,12 THE FIRST MC BASE FRACTURES.…”
Section: Diagnosismentioning
confidence: 99%
“…This type of injury accounts for 0.2% to 3% of patients visiting the emergency unit and 12% to 46% of all hand fractures [1]. Usually, younger patients are injured during sports activities, middle-aged patients are injured in manual labor, and elderly patients are most commonly injured when falling down [2].…”
Section: Introductionmentioning
confidence: 99%